Optimal time lags in panel studies - Dormann, C.; Griffin, Mark (2015)
© 2015 American Psychological Association. Cross-lagged regression coefficients are frequently used to test hypotheses in panel designs. However, these coefficients have particular properties making them difficult to interpret. In particular, cross-lagged regression coefficients may vary, depending on the respective time lags between different sets of measurement occasions. This article introduces the concept of an optimal time lag. Further, it is demonstrated that optimal time lags in panel studies are related to the stabilities of the variables investigated, and that in unidirectional systems, they may be unrelated to the size of possible true effects. The results presented also suggest that optimal time lags for panel designs are usually quite short. Implications are (a) that interpreting cross-lagged regression coefficients requires taking the time lag between measurement occasions into account, and (b) that in much research, far shorter time lags than those frequently found in the literature are justifiable, and we call for more "shortitudinal" studies in the future.